Perception of grief responses: Are maladaptive grief responses and the stages of grief considered normal?. Issue 6 (3rd July 2022) - McLean, Elisabeth; Singer, Jonathan; Laurita, Emily; Kahler, Julie; Levin, Crissa; Papa, Anthony
Abstract: Literature indicates laypeople hold strong opinions about how persons should grieve. This study examined how individuals perceive normal grief. Participants across two distinct samples (Study 1: N = 510 via MTurk; Study 2: N = 210 via Qualtrics panels) completed the Perception of Grief Scale and Grief Expectations Questionnaire. Findings indicated participants endorsed maladaptive grief responses as normal relative to other responses to loss. Endorsement of maladaptive grief responses as normal predicted endorsement of grief work beliefs. If social expectations deem maladaptive grief to be normal, as this study suggests, bereaved individuals might implicitly push themselves to grieve maladaptively.